Multi-impact performance of prestressed CFRP-strengthened RC beams using H-typed end anchors. (September 2022) - Huang, Zhenyu; Deng, Weixiong; Li, Ren; Chen, Jieren; Sui, Lili; Zhou, Yingwu; Zhao, Debo; Yang, Lei; Ye, Jianqiao
Abstract: To address the problem of insufficient ductility of traditional Carbon Fibre-reinforced polymer (CFRP) strengthened marine structures and to enhance the application of CFRP in marine engineering, the present study develops novel prestressed CFRP-strengthened RC beams using H-type end anchors with ductility controllable devices. In this device, part of the reinforcement bars are replaced by CFRP, which is prestressed as the structural enhancement material. The CFRP sheet is connected with a tensioned screw, which is used to realize the function of early warning based on a large plastic deformation when the structure is overloaded. Thus, the ductility of the composite structure could be improved based on yielding of the screw rod rather than the fracture failure of the CFRP sheet compared to that with CFRP bonded. This study investigates the flexural static and impact performance of the representative large-scale RC beams strengthened by prestressed CFRP through four-point bending and drop-weight impact. The results show that the H-typed end anchor and raising the prestress level of CFRP not only improve the ultimate resistance and ductility, but also realize the overload warning function under static load. Accordingly, the design still shows advantages in energy consumption and impact resistance through drop-weight impact. An advanced 3D nonlinear finite element model is built to simulate well the multiple impact performance in terms of the failure modes, impact force and displacement history. This study provides a new approach to address design deficiencies with insufficient ductility behaviour while using CFRP as a strengthening material. This prestressing technology is able to utilize the material efficiency of high-strength CFRP and open a new path for CFRP applications in marine civil engineering. Highlights: Develop a novel prestressed CFRP strengthened RC beam using ductile fused anchor. Perform flexural tests on novel prestressed CFRP strengthened RC beams. Perform multi-impact tests on novel prestressed CFRP strengthened RC beams. Provide a new FE simulation framework for multi-impact test. Analyze the time-lag between impact force and midspan displacement.